Visual Outcomes after Cataract Surgery in Diabetic Patients - Abdul Rehman; Bukhari, Sadia; Ali, Irshad; Hussain, Shuja; Bashir, Ihsan; Paras (Indus Journal of Bioscience Research, 2025)
Background: Diabetes mellitus accelerates cataract formation and may negatively affect postoperative visual recovery. Although cataract surgery significantly improves vision, the presence of diabetes-related ocular changes can influence outcomes. Objective: To evaluate the visual outcomes after cataract surgery in diabetic patients and identify factors associated with postoperative visual recovery. Methods: This descriptive study was conducted at the Diabetic Eye Clinic of Al-Ibrahim Eye Hospital, Karachi, from June 2023 to June 2024. A total of 133 diabetic patients aged 40–65 years undergoing cataract surgery were enrolled through non-probability consecutive sampling. Baseline demographics, duration of diabetes, and ocular examination findings were recorded. Visual acuity was assessed preoperatively and at postoperative day 1, week 1, and month 1. Results: The mean age of patients was 54.7 ± 6.8 years, with 72 (54.1%) males and 61 (45.9%) females. Preoperatively, 98 patients (73.7%) presented with severe visual impairment (<6/60). At one month postoperatively, 106 patients (79.7%) achieved visual acuity ≥6/18, while only 6 (4.5%) remained in the severe impairment category. Patients with diabetes <10 years had significantly better outcomes (88.9% achieving ≥6/18) compared to those with longer disease duration (73.4%, p = 0.03). Gender and education level did not significantly affect outcomes. Postoperative complications were infrequent, including transient corneal edema (6.8%) and posterior capsular opacification (3.8%). No case of endophthalmitis was observed. Conclusion: Cataract surgery in diabetic patients provides excellent visual outcomes, with most patients regaining functional vision. However, longer duration of diabetes is associated with poorer recovery, emphasizing the importance of early surgical intervention and careful preoperative evaluation.